Circulating Neutrophil Extracellular Traps as Diagnostic and Prognostic Markers for Inflammatory Bowel Disease: A Case-Control Study - Lu FY; Huang X; Zhang K; Yin X; Lv Y; Du YC; Zhou Q; Min JY; Cheng CE (Journal of Inflammation Research, 2025)
Fen-Ying Lu, Xia Huang, Ke Zhang, Xin Yin, Yang Lv, Yue-Chen Du, Qian Zhou, Jing-Yu Min, Cui-E Cheng Department of Gastroenterology, Affiliated Changshu Hospital of Nantong University (Changshu No. 2 People’s Hospital), Changshu, People’s Republic of ChinaCorrespondence: Cui-E Cheng, Email Cuie_cheng@163.comObjective: Current challenges in inflammatory bowel disease (IBD) treatment include the invasive nature of endoscopic evaluation, the gold standard for diagnosis, and the limited prognostic value of traditional inflammatory markers such as CRP and IL-6. This study aimed to explore the potential role of neutrophil extracellular traps (NETs) as biomarkers for the diagnosis, disease monitoring, and prognosis of IBD.Methods: A total of 100 patients with Crohn’s disease or ulcerative colitis and 100 healthy controls were recruited between June 2020 and September 2022. Clinical and laboratory data were collected, and patients with inactive IBD were followed for two years to assess factors influencing disease relapse.Results: Significant differences were observed in the levels of NETs markers and inflammatory cytokines among the three groups. Cell-free DNA (cfDNA), myeloperoxidase (MPO)-DNA complexes, and citrullinated histone 3 (CitH3) levels were significantly elevated in the active IBD group compared to the inactive IBD and healthy control groups (P < 0.001). Additionally, inflammatory cytokines such as C-reactive protein (CRP), vascular endothelial growth factor (VEGF), IL-1β, and IL-6 were also higher in the active IBD group (P < 0.001). A positive correlation was observed between circulating NETs markers and inflammatory cytokines. Multivariate analysis identified cfDNA (OR = 1.045), MPO-DNA (OR = 1.084), and CitH3 (OR = 2.871) as independent risk factors for IBD. Furthermore, patients with higher NETs scores experienced more frequent relapses. At the 1-year follow-up, the high-NETs group had 13 relapses compared to 5 in the low-NETs group (P = 0.026), and at the 2-year follow-up, 22 versus 14 relapses (P = 0.044).Conclusion: These findings suggest that NETs biomarkers may serve as effective diagnostic and prognostic tools for IBD, enabling early intervention and improved long-term management.Keywords: circulating NETs markers, inflammatory bowel disease, prognosis